0
$\begingroup$

I'm wondering how I would go about integrating this.

$\int (4x^2 - 3x + 2) / (4x^2 - 4x +3) dx$

I believe the right method would be to use partial fractions.. But if that is the case, I'm not sure how to do it. It's been quite some time since I've had to use said method.

Any help is greatly appreciated!

$\endgroup$
3
$\begingroup$

\begin{align} \int{\frac{4x^2-3x+2}{4x^2-4x+3}dx}&=\int{\frac{4x^2-4x+3+(x-1)}{4x^2-4x+3}dx}\\ &=\int{\left(1+\frac{x-\frac{1}{2}}{4x^2-4x+3}-\frac{\frac{1}{2}}{4x^2-4x+3}\right)dx}\\ &=x+\frac{1}{8}\ln(4x^2-4x+3)-\frac{1}{8}\int{\frac{1}{(x-\frac{1}{2})^2+\frac{1}{2}}dx}\\ &=x+\frac{1}{8}\ln(4x^2-4x+3)-\frac{\sqrt{2}}{8}\tan^{-1}[\sqrt{2}(x-\frac{1}{2})]+C \end{align}

$\endgroup$
0
$\begingroup$

$$f(x)=\dfrac{4 x^2-3 x+2}{4 x^2-4 x+3} =\dfrac{ x-1}{4 x^2-4 x+3}+1$$ Now $4 x^2-4 x+3$ is irreducible in $\mathbb R$, so we write $$\dfrac{ x-1}{4 x^2-4 x+3}=\dfrac{1}{8}\dfrac{ 8x-8}{4 x^2-4 x+3}=\dfrac{1}{8}\dfrac{ 8x-4}{4 x^2-4 x+3}-\dfrac{1}{2}\dfrac{ 1}{4 x^2-4 x+3}$$ Now $$\int \dfrac{ 8x-4}{4 x^2-4 x+3}dx=\log(|4 x^2-4 x+3|)$$ and $$\dfrac{ 1}{4 x^2-4 x+3}=\dfrac{ 1}{(2x-1)^2+2}=\dfrac{ 1}{2}\dfrac{ 1}{(\dfrac{2x-1}{\sqrt2})^2+1}$$ Now $$\int \dfrac{ 1}{(\dfrac{2x-1}{\sqrt2})^2+1}dx=\dfrac{\sqrt2}{2}tan^{-1}(\dfrac{2x-1}{\sqrt2}))$$ hence $$\int f(x)dx= \dfrac{1}{8}\log(|4 x^2-4 x+3|)+x-\dfrac{\sqrt2}{8}\; tan^{-1}(\dfrac{2 x-1}{\sqrt2})+constant$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.